In Search of Poverty Predictors: The Case of Urban and Rural Pakistan (The Pakistan Development Review, 2005)
The main objective of this research is to provide correlates of household consumption or poverty using the latest household survey. The estimated coefficients and their weights may be used to predict poverty incidence from light monitoring survey such as Core Welfare Indicator Questionnaire (CWIQ). The CWIQ survey instrument essentially collects simple welfare indicators from a large segment of population and is not designed to measure income, consumption or expenditure. The paper estimates consumption functions separately for urban and rural areas. These functions are estimatedwith the help of non-monetary correlates of consumption and applied to predict poverty at provincial and district levels. The paper also provides the latest estimates of poverty in the country using a consistent methodology. Overall, 33 percent people were poor, according to estimates from the latest available household survey of 2001-02. Incidence, depth, and severity of poverty are high in rural areas, as compared to their urban counterpart.